TRANSFORMASI KEPEMIMPINAN: MENGUKUR EFEKTIVITAS MANAJEMEN LAISSEZ-FAIRE DI LEMBAGA PENDIDIKAN - Yanto, Robi; Sirozi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Laissez-faire management is a leadership style that grants full autonomy to team members in decision-making and task execution. This study aims to evaluate the effectiveness of implementing laissez-faire management in educational institutions. The research employs a qualitative approach through literature review analysis. The findings reveal that this management style offers advantages, such as fostering creativity, innovation, individual independence, and enhancing personal responsibility among teachers. However, improper implementation may result in a lack of guidance, coordination, and accountability, negatively affecting educational quality. Factors such as school culture, teacher characteristics, facilities, and policy support significantly influence the effectiveness of this management style. This study recommends that educational leaders combine laissez-faire elements with other approaches to achieve an optimal balance between autonomy and supervision.